Cities of the gods : communist utopias in Greek thought - Dawson, Doyne (OUP E-Books., 1992)
This historical study of the theory of Utopian communism in ancient Greek thought identifies and assesses the reasons for the decline in Utopian traditions after 150 BC. The author examines the evidence of the survival of Utopian traditions; particularly their influence on early Christianity.